Differential flight muscle development in workers, queens and males of the eusocial bees, Apis mellifera and Scaptotrigona postica - Correa-Fernandez, Fernanda [UNESP]; Cruz-Landim, Carminda [UNESP] (Univ Arizona, 2010)
The flight capability of the adult eusocial bees, Apis mellifera L. and Scaptotrigona postica Latreille (Hymenoptera: Apidae), is intrinsically linked to their colonial functions, such as the nuptial flight for mating in the case of queens and males, and the exploration of new habitats for nesting and food sources in the case of workers. Flight is achieved by the contraction of indirect flight muscles that produce changes in thoracic volume and, therefore, wing movement. The purpose of this work is to examine possible differences in muscle development that may be associated with the flying activity of individuals in a given life stage considering the behavioral and physiological differences among the stages and between the two species studied. Measurements of the muscle fibers obtained from light microscopy preparations of muscle were submitted to statistical analysis in order to detect the differences at a given time, or throughout the life of the individual. The results show that muscle morphology is similar in both species, but in A. mellifera the muscle fibers are thicker and more numerous than in S. postica. Differences in the fiber thickness according to life stage in all classes of individuals of both species were detected. These results are discussed in relation to the need for flying in each life stage.
Keywords: Flight muscles; histology; morphometry; male; queen; worker